2020
DOI: 10.5267/j.msl.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of perceived quality and perceived value on customer satisfaction

Abstract: This empirical study aims to identify the effects of different factors influencing on customer satisfaction, such as perceived quality or perceived value in a case study in chemical industry. Understanding the effects of such variables helps us manage customers properly, balancing between perceived quality and perceived value. The research design is a quantitative method and employs Structural Equation Method (SEM) to ensure the correlation between constructs. The method results confirm that perceived value co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
21
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 34 publications
7
21
0
4
Order By: Relevance
“…Satisfaction (β 4 ) = 0.047 or 4.7%, which shows that one-percent increase in satisfaction of customers increases 4.7% of customer retention level because of its positive beta value if the remaining variables remained controlled.is shows that there is a positive relationship between satisfaction and customer retention and satisfaction has clear significant effect on customer retention. is result maintains what is stated with studies done in[21][22][23]30].…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Satisfaction (β 4 ) = 0.047 or 4.7%, which shows that one-percent increase in satisfaction of customers increases 4.7% of customer retention level because of its positive beta value if the remaining variables remained controlled.is shows that there is a positive relationship between satisfaction and customer retention and satisfaction has clear significant effect on customer retention. is result maintains what is stated with studies done in[21][22][23]30].…”
supporting
confidence: 90%
“…It was proposed that when perceived service quality is high, then it will lead to increase in customer satisfaction. Several researchers found that customer satisfaction significantly influences customer retention in various sectors, namely, insurance company [21], life insurance services [22], and banking [19,23] and also argued that customer satisfaction will improve customer retention. is has resulted in the following hypothesis: H 4 : customer satisfaction has a significant effect on customer retention.…”
Section: Relationship Between Satisfaction and Customermentioning
confidence: 99%
“…According to Reid and Sanders (2011) factors such as product design and quality; competitive pricing, and ability of products/services to fulfill market need promote customer satisfaction. Factors such as cycle time and timely delivery of products contribute to service quality, which enhances customer satisfaction (Samudro et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perceived value is a trade-off between total benefits received and total sacrifice by considering a supplier's offering and price (Lam et al, 2004;Samudro et al, 2020Samudro et al, , 2018b. Although sacrifice can be in either monetary or non-monetary terms (Mayr et al, 2012), Patterson and Spreng et al, 1997, p. 424) claim that emotional elements may not be relevant in an industrial relationship.…”
Section: Perceived Valuementioning
confidence: 99%